2020
DOI: 10.18484/2305-0047.2020.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities of EVLA in Complex Treatment of Venous Trophic Ulcers in Aged and Senile Patients

Abstract: Цель. Оптимизировать результаты комплексного лечения декомпенсированных форм варикозной болезни нижних конечностей у пациентов пожилого и старческого возраста.Материал и методы. Проанализировали результаты комплексного лечения 15 пациентов пожилого и старческого возраста с венозными трофическими язвами нижних конечностей (клинический класс С6 по СЕАР) с применением стволовой эндовазальной лазерной облитерации. Средний возраст пациентов составил 74,1±4,76 года (M±σ). Язвы существовали от 10 до 18 лет. Эндовазал… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
0
1
Order By: Relevance
“…The link between TT, INR, and prognosis in COVID19-infected patients is relatively uncommon compared to other coagulation parameters, such as D-D. However, while several studies have found a frequent connection between abnormally high TT and INR levels and increased mortality 14,[22][23][24] , our research does not support this nding. Nonetheless, there is limited evidence to investigate their time-varying trend.…”
Section: Discussioncontrasting
confidence: 95%
“…The link between TT, INR, and prognosis in COVID19-infected patients is relatively uncommon compared to other coagulation parameters, such as D-D. However, while several studies have found a frequent connection between abnormally high TT and INR levels and increased mortality 14,[22][23][24] , our research does not support this nding. Nonetheless, there is limited evidence to investigate their time-varying trend.…”
Section: Discussioncontrasting
confidence: 95%